Prevalence of dyslipidemia and its influencing factors among adult residents in Hebei province: a cross-sectional survey - Qianyu LI; Yajing CAO; Lijuan TANG; Yuhuan LIU; Xiaoying LU; Qi QI; Shifan WANG; Xiaoli LIU; Ze CUI (Zhongguo gonggong weisheng)
ObjectiveTo investigate the prevalence of dyslipidemia and its influencing factors among adults in Hebei province, to provide a reference for the prevention and control of dyslipidemia in the population. MethodsFrom September 2020 to June 2021, 12 187 permanent residents aged ≥ 18 years were recruited from 60 rural villages/urban communities in 10 counties/districts of Hebei province using a stratified multistage random sampling method and underwent in-person questionnaire interview, physical examination, and laboratory tests. The prevalence of dyslipidemia and its components was analyzed, and an unconditional multivariate logistic regression model was used to analyze the main factors influencing dyslipidemia and its components in the participants. Results Among all the participants, the prevalence of dyslipidemia was 32.8% and the prevalence rates of hypercholesterolemia, hypertriglyceridemia, hyper-low-density lipoprotein cholesterolemia (LDL-C), and hypo-high-density lipoprotein cholesterolemia (HDL-C) were 5.4%, 14.0%, 4.8%, and 15.5%, respectively. Unconditional multivariate logistic regression analysis showed that among adult residents, age ≥ 25 years, current smoking, overweight, obesity, central obesity, body fat percentage ≥ 27.2%, and basal metabolic rate ≥ 1 504 kcal were risk factors for dyslipidemia, whereas female gender, rural residence, and sedentary time of 2 – 4 hours per day were protective factors against dyslipidemia; age ≥ 25 years, college education or higher, current smoking, central obesity, and body fat percentage ≥ 37.9% were risk factors for hypercholesterolemia, whereas a basal metabolic rate of 1 199 – 1 503 kcal was a protective factor; age 25 – 64 years, current smoking, consumption of animal and poultry meat 300 – 500 g per week, overweight, obesity, central obesity, and body fat percentage ≥ 27.2% were risk factors, whereas female gender was a protective factor for hypertriglyceridemia; age ≥ 25 years, central obesity, sedentary time ≥ 2 hours per day, and body fat percentage ≥ 37.9% were risk factors, whereas basal metabolic rate 1 199 – 1 503 kcal was a protective factor for hyper-LDL-C; ethnic minority, current smoking, overweight, obesity, central obesity, physical inactivity, body fat percentage 33.0% – 37.8%, and basal metabolic rate ≥ 1 327 kcal were risk factors, whereas being female, aged 45 – 54 years, living in rural areas, drinking alcohol, consuming livestock and poultry meat > 500 g per week, and being sedentary for ≥ 2 hours per day were protective factors for hypo-HDL-C. ConclusionsThe prevalence of dyslipidemia in adults in Hebei province is relatively low. Sex, age, place of residence, current smoking, body mass index, central obesity, sedentary behavior time, body fat percentage, and basal metabolic rate are the main influencing factors of dyslipidemia in adults in this region.